The Impact Of Climate Change On Food Security And Health, Case Of Algeria - Kaabache, Rachida; Badaoui, Brahim (جامعة الوادي - University of Eloued, 2022)
Global warming, as a modern issue faced by humanity, is following a pace considered to be the fastest since the last ten thousand years. It is caused by climate fluctuations, but also human activity; exposing the world population to food insecurity, famines and transmissible diseases… Particularly in the developing world, where populations are already living in a precarious situation. Our country witnesses its effects through lower precipitations, which can affect its water capacities and the agricultural production volume, with a direct impact on its food security. A situation causing the food bill to rise constantly in order to guarantee food availability for its population. Therefore, the solution could be the implementation of a new agrarian policy, enabling a sustainable management of its existing resources. That may revive an agriculture that is still suffering from the negative effects of colonization. Throughout this article, we will try to discuss the impact climate change has on food security and populations‟ health, while highlighting the importance of the agrarian policy as a way to tackle the issue
مقال
Keywords: Climate Change ; Food Security ; Health ; Agrarian Policy ; Algeria